Never Say Never : A Novel - Steel, Danielle (New York, New York : Delacorte Press, 2025)
Oona Kelly Webster has much to be grateful for. A striking woman with red hair and green eyes, she has a loving family and a job she adores, editing a prestigious line of books. To celebrate their twenty-fifth wedding anniversary, she and her husband, Charles, have planned a visit to France. But then Charles drops a bombshell. He has been living a lie--hiding an affair for a year--and he is leaving Oona for a younger male lover.
new book 2025 winter.
Keywords: Man-woman relationships -- Fiction; Adultery -- Fiction; Motion picture actors and actresses -- Fiction; Interpersonal relations -- Fiction; Life change events -- Fiction; Betrayal -- Fiction; France -- Fiction; Romance fiction